Bolha informacional e a relevância das informações dos sites de redes sociais para os adolescentes brasileiros - Faria Lopes, Deusdedit; Franklin Frogeri, Rodrigo; Souza, Mariana Aranha de; dos Santos Portugal Júnior, Pedro (Teknokultura. Revista de Cultura Digital y Movimientos Sociales, 2023)
The objective of this study was to investigate the relationship between the sources of information young people use to stay informed of current affairs and the importance/relevance of this information to their everyday lives. The study included a sample of 1,361 respondents and used Structural Equation Modeling – Path analysis. The results suggest that the Social Networking Site (SNS) TikTok has a greater ability to create a perception of relevance/importance of the content being consumed by its users. This perception may be associated with this SNS’s ability to go beyond the creation of informational bubbles and act as a sociotechnical system that stimulates certain affective responses. Furthermore, we observed that TikTok and Facebook, respectively, are more influential than Instagram, WhatsApp, and YouTube in the gatekeeping process, and thus, information from these sources is considered more relevant/important by teenagers.
Keywords: digital communication; fiter bubble; network gatekeeping theory; TikTok; Facebook